E-Chord: Keyword-Based Search Algorithm Based on DHT in Mediation Architecture - Kharma, Qasem; Ege, Raimund; Shaar, Said Abu (INFOCOMP Journal of Computer Science, 2007)
E-Chord is a Distributed Hash Table algorithm (DHT) inspired from Chord, Pastry and CAN algorithms. It meant to provide a keyword-based search in the Three-Layer Mediation Architecture. The E-Chord is deployed in the middle layer (Integration Layer) of the architecture and provides services to the higher layer (Presence Layer) and the lower layer (Homogenization Layer).